Exploring numeracy teaching and learning by using ethnomathematics - Mukwambo, Muzwa; Zulu, Africa; Kayangula, Manyando (International Journal on Teaching and Learning Mathematics, 2023)
The purpose of this study was to explore the impact that the cultural or everyday practices of ethnomathematics of a particular cultural group will have if they are used in teaching and learning of numeracy concepts related to geometrical shapes. It explored cultural practices, artefacts, written, verbal or visual communication messages reflecting mathematics in order to see how they could best eliminate the problems learners encounter in the acquisition of numeracy language. Data was generated using observations, brainstorming and interviews. Based on this research, the impact of using ethnomathematics in numeracy teaching and learning brings in innumerable benefits. These include promoting deep learning and allows teachers to maka use of prior knowledge in the classroom. This allows learners to recall and relate to the concepts learnt and employ them in their daily activities so that they do not to remain inert. Another impact of interest was the reclaiming of names of geometrical shapes from certain languages which currently teachers are not aware of as they are overlooked. For instance when geometrical shapes were first discussed using local terminology, it made more meaning than when taught using English used as a medium of teaching and learning in the research area.